The role of Foreign Direct Investment (FDI) in a dualistic growth framework: A smooth coefficient semi-parametric approach - Zeb Aurangzeb; Thanasis Stengos (Borsa Istanbul Review, 2014)
This paper examines the relationship between Foreign Direct Investment (FDI) and economic growth. We extend the dualistic growth framework by Feder (1982), whereby we divide the economy into an exports and a non-exports sector and assume that the FDI is mainly entering the former. In order to empirically estimate the effects of FDI on economic growth, we employ a smooth coefficient semi-parametric approach. Our results show that countries with higher levels of FDI inflows experience higher productivity in the exports sector as compared with those with low level of FDI inflows. In general, we provide some evidence that FDI inflows play an important role during the development process: Initially, as an important determinant of growth, later on, by helping improve factor productivity in the exports sector and finally, through spillover effects due to fostering the linkages between the Multinational Corporations (MNC) and their host economy partners.